NILAI AGAMA DAN BUDAYA DALAM TRADISI BESAMAN - Angga Marzuki (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
This paper discusses the Besaman Ritual practice on Lingga Island, specifically in the Kelumu Village. Culture and tradition are the heritage and identity of a nation, both are passed down from generation to generation. It is not a static thing but dynamic. Although the change is not so big, but tradition allows to have changes to adapt to the context of the times and geographical conditions. Similar to similar practice in other places in the country, the Besaman tradition in Lingga Island, in Kelumu Village is the reading of Ratib Sammān. By conducting in-depth interviews and analyzing the data collected, this study finds that the implementation of this tradition contains the values of Religion and Education and several aspects of this tradition adapt to context.